10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Increasing global evidence highlights the significant intersections between violence against women (VAW) and violence against children (VAC), emphasising the need for collaboration among actors addressing VAW and VAC. However, tensions regarding prioritising women's and children's needs have led to fragmented approaches, in addition to knowledge gaps regarding effective collaborative efforts. This study aims to assess how the coordination between VAW and VAC programmes is conceptualised and operationalised in Iraq, Jordan, and Lebanon. Specifically, it seeks to identify a) how VAW and VAC collaboration is understood, b) challenges to its implementation, and c) recommendations for strengthening it. We conducted a situation analysis utilising document review and qualitative interviews. A policy document analysis was conducted across the study countries. Thirty key informant interviews were conducted with stakeholders selected based on their experience in VAW and/or VAC work. Data were analysed thematically. Collaboration between efforts to address VAW and VAC was frequently described at the policy level through integrated, multi-sectoral family protection approaches, particularly in Lebanon and Jordan. Overall, few programmes and services adopted a coordinated approach to VAC and VAW, with varying concept understanding and quality across the three countries. A key cross-country finding was that VAC is often positioned as a more socially and politically acceptable entry point for addressing family violence, allowing actors to indirectly engage with VAW in cultural contexts where gender norms constrain specifically addressing VAW. Recommended opportunities for simultaneously preventing VAC and VAW included community-based youth programs, parenting initiatives, and involvement of cultural and religious leaders. The study highlights existing, albeit limited, coordinated approaches to addressing VAW and VAC in the three settings, however, their implementation is constrained by structural and systemic barriers. Given ongoing resource limitations,identifying interventions that can safely address both VAW and VAC outcomes is critical, when appropriate and safe to do so.